Recursos didácticos digitales en la construcción del conocimiento matemático en el contexto de la educación en modalidad híbrida para los estudiantes del segundo año de educación general básica de la escuela “Continental School” del cantón Píllaro provincia de Tungurahua durante el año lectivo 2021-2022 - Figueroa Chango, Katherine Natalia (2022)
10 ABSTRACT This research work was carried out thinking about the current situation of COVID 19, which resulted in a great change in the different spaces of society. However, education turned out to be a weak point since most teachers and students were not prepared to move to a virtual modality. That is why an investigation is started at the Escuela de Educación Básica Continental School of the Píllaro canton, province of Tungurahua, with the theme Digital didactic resources in the construction of Mathematical knowledge in the context of hybrid modality education, especially in the second year. . For this, the methodology used is based on the qualitative- quantitative method, the research design is exploratory sequential, typical of the mixed approach and participation in the place of research, the bibliographic method is important to support the scientific theory, as well as the logical history that allowed knowing the importance of this research, the deductive and inductive methods to generate conclusions from the general to the particular and vice versa. For the data collection, an interview with the teacher was intervened, consisting of ten open questions regarding the subject of the investigation, this activity was carried out in person. While the non-participant observation sheets addressed to the students are proposed for the hybrid context, that is, the information collected was presidential and virtual, where each class was observed and analyzed according to the student's behavior. The population and participating sample was 22 students and the teacher of the course. Among the results obtained, it is evident that the teacher uses as a digital didactic resource the platform that consists of the book with limited activities that do not allow the free exploration of the student, being a character in the process of learning, she is curious to know beyond what is provided. Activities that allow you to develop technological skills, mathematical logical knowledge and problem solving together with technology.